(untitled) (Marketing Journal, 2025)
This article analyzes the current state of marketing processes and development prospects at grain products manufacturing enterprises. Within the scope of the research, modern marketing strategies, digital marketing tools, market segmentation, and branding directions have been studied. The article reviews the application of Customer Relationship Management (CRM), digital transformation, and omnikanal marketing in the grain processing industry. Research results show that an integrated marketing strategy allow s increasing market share by 15 -25% and improving customer loyalty by 30-40%. № 1 501